Media, art and technology: a contemporary reflection - Lopes, Fernando Augusto Silva (2017)
This article is based on a report about cultural industries and their reflexes on media saturation. From that point, a reflection on technology, media and contemporary arts is presented, especially on the role of the body in the manifestation of art. This work seeks to ratify the influence of technology, of mass media and of information over the construction of the contemporary cultural values. It also provides a reflection on current contemporary artistic practices as elements that seek to evidence and question the standardizing influence of mass media and of the market. The background for the development of this article is the evolution of technologies, which expand the commodification of culture and make possible the deep social and cultural changes experienced in contemporary Western society. Finally, it is outlined a brief analysis  of cultural identities and diversities in the teleinformatics era.